Opposing effects of rheumatoid arthritis and low dose prednisolone on arginine metabolomics. (November 2017) - Radhakutty, Anjana; Mangelsdorf, Brenda L.; Drake, Sophie M.; Rowland, Andrew; Smith, Malcolm D.; Mangoni, Arduino A.; Thompson, Campbell H.; Burt, Morton G.
Abstract: Background and aims: The effects of low dose prednisolone on circulating markers of endothelial function, the arginine metabolites asymmetric dimethyl arginine (ADMA), mono methyl arginine (MMA), and homoarginine, are uncertain. We assessed whether patients with rheumatoid arthritis have perturbations in arginine metabolite concentrations that are reversed by low dose prednisolone. Methods: Eighteen rheumatoid arthritis patients who had not taken prednisolone for >6 months (non-glucocorticoid (GC) users), 18 rheumatoid arthritis patients taking continuous oral prednisolone (6.5 ± 1.8 mg/day) for >6 months (GC users) and 20 healthy controls were studied. Fasting plasma concentrations of ADMA, MMA, and homoarginine were measured by ultra-performance liquid-chromatography. Baseline data from non-GC users were compared with healthy controls to assess the effect of rheumatoid arthritis. The change in arginine metabolites in non-GC users after 7 days of prednisolone (6 mg/day) was used to assess the acute effects of prednisolone. Baseline data from non-GC users were compared with GC users to assess the chronic effects of prednisolone. Results: Non-GC users had higher ADMA (0.59 ± 0.03 vs. 0.47 ± 0.01 μM, p  = 0.004) and MMA concentrations (0.10 ± 0.01 vs. 0.05 ± 0.00 μM, p < 0.001) than controls. The only change with acute prednisolone was a reduction in homoarginine (1.23 ± 0.06 vs. 1.08 ± 0.06 μM, p  = 0.04) versus baseline. GC users had lower concentrations of ADMA (0.51 ± 0.02 vs. 0.59 ± 0.03 μM, p  = 0.03) than non-GC users. Conclusions: Rheumatoid arthritis patients have higher concentrations of ADMA and MMA, inhibitors of endothelial function. Chronic, but not acute, prednisolone therapy is associated with a lower ADMA concentration, suggesting a salutary effect of long-term glucocorticoid treatment on endothelial function. Highlights: ADMA, a marker of endothelial dysfunction, is increased in rheumatoid arthritis. Acute prednisolone in rheumatoid arthritis reduces plasma homoarginine. Long-term prednisolone is associated with lower ADMA.